PROBLEMATIKA PEMBELAJARAN BAHASA ARAB DI SEKOLAH DASAR ISLAM PLUS AL-ITTIBA’ JUWIRING KLATEN - Fahmi, Muhammad; Putra, Sudarmadi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This study aims to describe the process of learning Arabic, the problems encountered, the solutions made to overcome these problems and the curriculum targets at Al-Ittiba'Juwiring Klaten Islamic Elementary School Plus. This study uses a descriptive qualitative approach. Data collection techniques carried out are through observation, interviews and documentation. Data analysis methods are used by collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the implementation of learning Arabic at the Islamic Elementary School Plus Al-Ittiba' Juwiring Klaten begins with the teacher reading and explaining the material, then students are given assignments using an Arabic language textbook published by Pustaka Sofwa. The problem faced in learning Arabic is that Arabic teachers are not graduates of Arabic language education study programs. Then, students are not enthusiastic in learning Arabic because the learning method is monotonous. So on, less time is facilitated and the curriculum uses an old curriculum. The solution is that the Arabic teacher should be a graduate of Arabic language education study program. Then, the teacher should motivate students more often and the methods used should be more varied. Then, the time facilitated in learning is added and the curriculum used should use the latest curriculum. The aim of the curriculum is to foster students to become intelligent, Muslim and noble human beings